COMMUTING TRACES OF SYMMETRIC LEFT BICENTRALIZER ON SEMIPRIME RINGS - H. Majeed, Abdul-Rahman.; Mahmood, Auday Hekmat (MAGISTRA, 2015)
Let R be an associative ring. The purpose of this paper is to study the investigate identitiessatisfied by symmetric left Bicentralizer on a semiprime rings which make the trace of such mappings iscommuting on R.Key words and phrases: Semiprime rings, symmetric left Bicentralizer, trace of biadditive mappings, commutingmapping.